Comparison of Serum Interleukin 10 Levels between Leprosy and Non-Leprosy Population - Kodrati, Adika; Salim, Eddy Mart; Hafy, Zen (Universitas Muhammadiyah Yogyakarta, 2021)
Leprosy is a chronic granulomatous infectious disease that attacks the peripheral nerves, skin, and other organs. The cytokine IL-10 can deactivate macrophages, inhibit IL-12 production, which also inhibits IFN-Ï’ production. IL-10 directly inhibits CD4+T cells and antigen-presenting cell (APC) function in cells infected withÂ M. leprae. The purpose of this study was to determine the differences in IL-10 levels in leprosy patients and non-patients at dr. Mohammad Hoesin Palembang Hospital. This study used a case-control design for comparing 2 groups. Respondents in this study were 80 people. The case samples were all leprosy patients who were treated at the dr. Mohammad Hoesin Hospital, Palembang for the period of January 16 - February 16, 2019, while the control group was medical personnel and paramedics who worked at the same hospital. The examination was carried out using the ELISA Sandwich method. The results showed that there was a significant difference in IL-10 levels between leprosy patients and non-leprosy leprosy (p=0.000). The average IL-10 level in leprosy patients (13.24 pg/ml) was lower than that in non-patients (40.15 pg/ml). It is concluded that there is a difference in IL-10 levels between leprosy patients and non-leprosy patients in leprosy sufferers are lower than non-leprosy persons.Â